Effect of Silica Fillers on Characterization of Cellulose-Acrylamide Hydrogels Matrices as Controlled Release Agents for Urea Fertilizers - Deni Swantomo; Rochmadi Rochmadi; Kris Tri Basuki; Rahman Sudiyo (Indonesian Journal of Chemistry, 2014)
Controlled Release Urea Fertilizers-based hydrogels matrices was synthesized by graft copolymerization of acrylamide onto the rice straw cellulose backbones in the presence of silica fillers using simultaneous graft copolymerization by gamma irradiation as initiator. Evidence of the silica presence on grafted cellulose was obtained from FTIR. X-ray diffraction analysis showed that the crystalline was reduced through silica fillers added. The effect of silica content on grafting efficiency, gel fraction, Young modulus, swelling degree, and urea loading were examined. It was found that grafting efficiency and gel fraction decrease with increasing silica added inversely with Young modulus. Water swelling and loading urea fertilizers into hydrogels matrices were conducted and the results showed that swelling degree and urea fertilizers loading increased first and then decreased with increasing silica added. The effect of the silica fillers had implications in the mechanism of controlled release urea fertilizers that diffusion-controlled mechanism became dominant, which attributed to the decreasing of urea diffusion coefficient.